A folded cascade-based broadband transimpedance amplifier for optical communication systems. (August 2016) - Rakide, Majid; Seifouri, Mahmood; Amiri, Parviz
Abstract: This paper presents a high gain CMOS transimpedance amplifier (TIA) design using staggering technique to obtain high bandwidth and low gain ripple. To provide the staggered frequency response, the proposed TIA employs a π -network as a transimpedance stage along with a novel Folded Cascade-based shunt amplifier as a post amplifier stage. Simulation of the proposed TIA for 1.8 V 0.18 μm CMOS technology shows that a gain of 58 dB Ω with 1 dB Ω gain-ripple over a bandwidth of 8.1 GHz can be achieved while the whole TIA circuit consumes 38.2 mW from 1.8 V power supply. The simulated average input noise current spectral density is about 15 pA / Hz within the TIA frequency band.